Cosmopolitan political thought method, practice, discipline - Godrej, Farah (New York ; Oxford : Oxford University Press, 2011)
This title is a normative argument for applying the idea of cosmopolitanism to the discipline of political theory itself. It is inspired by two recent turns in political thought.
Also issued in print format.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy; Cosmopolitanism